Time trends, projections, and spatial distribution of low birthweight in Australia, 2009–2030: Evidence from the National Perinatal Data Collection. Issue 1 (25th January 2023) - Huda, M. Mamun; Callaway, Leonie K.; Jackson, Greg; Fatima, Yaqoot; Cumming, Janet; Biswas, Tuhin; Paz, Gonzalo R.; Boyle, Fran; Sly, Peter D.; Mamun, Abdullah Al
Abstract: Introduction: Infants with low birthweight (LBW, birthweight <2500 g) have increased in many high‐resource countries over the past two decades. This study aimed to investigate the time trends, projections, and spatial distribution of LBW in Australia, 2009–2030. Methods: We used standard aggregate data on 3 346 808 births from 2009 to 2019 from Australia's National Perinatal Data Collection. Bayesian linear regression model was used to estimate the trends in the prevalence of LBW in Australia. Results: Wefound that the prevalence of LBW was 6.18% in 2009, which has increased to 6.64% in 2019 (average annual rate of change, AARC = +0.76%). If the national trend remains the same, the projected prevalence of LBW in Australia will increase to 7.34% (95% uncertainty interval, UI = 6.99, 7.68) in 2030. Observing AARC across different subpopulations, the trend of LBW was stable among Indigenous mothers, whereas it increased among non‐Indigenous mothers (AARC = +0.81%). There is also an increase among the most disadvantaged mothers (AARC = +1.08%), birthing people in either of two extreme age groups (AARC = +1.99% and +1.53% for <20 years and ≥40 years, respectively), and mothers who smoked during pregnancy (AARC = +1.52%). Spatiotemporal maps showed that some of the Statistical Area level 3 (SA3) in Northern Territory and Queensland had consistently higher prevalence for LBW than the national average from 2014 to 2019. Conclusion: Overall, the prevalence of LBW has increased in Australia during 2009–2019; however, the trends vary across different subpopulations. If trends persist, Australia will not achieve the Sustainable Development Goals (SDGs) target of a 30% reduction in LBW by 2030. Centering and supporting the most vulnerable subpopulations is vital to progress the SDGs and improves perinatal and infant health in Australia.